Designing supplementary speaking materials based on communicative language teaching (CLT) - Efendi, Mutiara Yulia; Robiasih, Hasti (Universitas Sarjanawiyata Tamansiswa, 2021)
Abstract: This research aims at designing supplementary speaking materials for seventh-grade students of SMP Islam Al Azhar 34 Bintan in conjunction with communicative language teaching (CLT) and the efficacy of supplementary speaking materials to improve students’ speaking skills. This research adapted Borg and Gall’s research and information collection, planning, product development, preliminary field testing, main product revision, and final product revision models. Data were collected from document analysis, classroom observation, and interviews to set up the goals. The findings showed that the designed supplementary speaking materials reflected the efficacy of students’ improvement using the communicative language teaching approach. The materials were beneficial and attractive to students in teaching and learning English involvement. Keywords: CLT, junior high school, supplementary speaking materials.